Konceptualizacja zmysłów w twórczości Adama Mickiewicza = Conceptualization of senses in Mickiewicz's output - Kładoczny, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Linguists can reconstruct a conceptualization of senses in Adam Mickiewicz's writings on the basis of the writer's language dictionary. Lexicon characterizing each sense were arranged in semantic categories connected with one another, which construct a frame semantic. The writer was susceptible to each of senses but most often he referred to sight and hearing. Mickiewicz used a complete variety of words specific to his epoch. Adam Mickiewicz didn't form new words in the studied range of vocabulary.
Keywords: Mickiewicz, Adam (1798-1855); zmysły; konceptualizacja; rama interpretacyjna; nazwy dźwięków; senses; conceptualization; semantic frame; sounds names